Beta-adrenergic function in airways of healthy and asthmatic subjects. - Gayrard, P (1975)
We measured the short-term effects of beta-adrenergic blockade with propranolol (0.2 mg/kg iv), followed by stimulation with salbutamol (200 mug inhaled), on specific airway conductance (SGaw) heart rate, and systemic blood pressure (BP) in 11 healthy subjects, and 11 symptom-free asthmatics with normal lung function values. Propranolol induced a significant bronchoconstrictor effect in both groups, stronger in asthmatics than in normals: mean SGaw decreased 34.6 +/- 25% against 9.4 +/- 9% (p less than 0.01). Six of the 11 asthmatics exhibited a more pronounced bronchoconstriction than the most responsive healthy subject. Large individual variations were seen in both groups although they were greater in the asthmatics. A similar rise in SGaw was produced by salbutamol in both groups. The decrease of heart rate provoked by propranolol was similar in the two groups, averaging 18.6%, with no further change after salbutamol. The blood pressure was slightly decreased by propranolol in both groups. The results indicate that normal subjects have a weak and variable bronchodilator beta-adrenergic activity. In most asthmatics beta-adrenergic tone appeared more pronounced. The individual differences in response to propranolol observed in both groups suggest that asthmatic patients differ quantitatively rather than qualitatively from healthy subjects with respect to beta-adrenergic receptor function. There was no association between clinical findings and the degree of bronchomotor effect of propranolol in the patients with asthma. This study does not support the view that airways of asthmatic patients have a decreased beta-adrengeric receptor function.